Improved Cuckoo Search Algorithm for Nonconvex Hydrothermal Scheduling with Volume Constraint - Nguyen, Thang Trung; Vo, Dieu Ngoc; Deveikis, Tomas; Rozanskiene, Arnolda (Elektronika ir Elektrotechnika, 2017)
This paper presents an improved cuckoo search algorithm (ICSA) for solving the short-term hydrothermal scheduling (ST-HTS) problem. In the proposed ICSA, the initial eggs are first classified into two groups including top group and abandoned group and each egg in the two groups is then newly generated via Lévy flights. The two new egg groups will be integrated into only one group before ranking and evaluating to choose the best egg, which will be used to generate new eggs via the action of discovery of alien eggs in the host bird’s nest. Moreover, the fraction of the alien eggs to be abandoned will be adaptive at each iteration instead of a fixed value during the search process like the conventional Cuckoo Search Algorithm (CSA). The performance of the proposed ICSA has been tested on two different systems and the obtained results have been compared to those from many methods including CSA, modified CSA and other methods in the literature in terms of solution quality. The result comparison has revealed that the proposed ICSA is very efficient for solving the ST-HTS with reservoir storage constraints. DOI: http://dx.doi.org/10.5755/j01.eie.23.3.12657